COMPRESSION STRENGTH OF STRUCTURAL LIGHTWEIGHT CONCRETE, WHEN REPLACING THE COARSE AGGREGATE BY SATURATED AND DRY TRACHITE (LACCEI, 2024)
The research exposes the results of the study carried out to determine the compressive strength of a structural lightweight concrete, by replacing the coarse aggregate with saturated and dry trachyte. The evaluation was carried out by comparing the standard sample that contains 20% expansive clay as part of the cement, with the (4) treatments that contain expanded clay and a percentage of replacement of the coarse aggregate by trachyte. The tests consisted of making concrete specimens with f'c= 210 kg/cm², to later evaluate the compressive strength at the age of 7, 14 and 28 days and the volumetric weight in its fresh and hardened state. From the results, it was concluded that when the coarse aggregate is replaced by 3% and 5% saturated and dry trachyte, the compressive strength increases by 1.3%, 6.5%, 2.6% and 6.2%, respectively. And that the influence on the volumetric weight by replacing the coarse aggregate with 3% and 5% saturated trachyte increases by 1.48% and 1.79% respectively, while with the replacement of 3% and 5% dry trachyte, the volumetric weight decreases in 0.84% ​​and 0.83% respectively